Liquid–liquid diffusion crystallization improves the X‐ray diffraction of EndoS, an endo‐β‐N‐acetylglucosaminidase from Streptococcus pyogenes with activity on human IgG. Issue 12 (1st December 2013) - Trastoy, Beatriz; Lomino, Joseph V.; Wang, Lai‐Xi; Sundberg, Eric J.
<x xml:space="preserve">Abstract</x> Endoglycosidase S (EndoS) is an enzyme secreted by Streptococcus pyogenes that specifically hydrolyzes the β‐1, 4‐di‐N‐acetylchitobiose core glycan on immunoglobulin G (IgG) antibodies. One of the most common human pathogens and the cause of group A streptococcal infections, S. pyogenes secretes EndoS in order to evade the host immune system by rendering IgG effector mechanisms dysfunctional. On account of its specificity for IgG, EndoS has also been used extensively for chemoenzymatic synthesis of homogeneous IgG glycoprotein preparations and is being developed as a novel therapeutic for a wide range of autoimmune diseases. The structural basis of its enzymatic activity and substrate specificity, however, remains unknown. Here, the purification and crystallization of EndoS are reported. Using traditional hanging‐drop and sitting‐drop vapor‐diffusion crystallization, crystals of EndoS were grown that diffracted to a maximum of 3.5 Å resolution but suffered from severe anisotropy, the data from which could only be reasonably processed to 7.5 Å resolution. When EndoS was crystallized by liquid–liquid diffusion, it was possible to grow crystals with a different space group to those obtained by vapor diffusion. Crystals of wild‐type endoglycosidase and glycosynthase constructs of EndoS grown by liquid–liquid diffusion diffracted to 2.6 and 1.9 Å resolution, respectively, with a greatly diminished anisotropy. Despite extensive efforts, the failure to reproduce these liquid–liquid diffusion‐grown crystals by vapor diffusion suggests that these crystallization methods each sample a distinct crystallization space.